Laparoscopic assisted transanal pull through and Duhamel pull through for the treatment of short segment Hirschsprung’s disease: A comparative study of outcome - Shahid, Shah Md Ahsan; Ali, Md Nowshad; Nasrin, Khondokar Seheli; Paul, Shantona Rani; Hossain, Md Zamil (Journal of Paediatric Surgeons of Bangladesh, 2023)
Background: The goal of surgical management for Hirschsprung’s disease is to remove the aganglionic bowel and reconstruct the intestinal tract by bringing the normally innervated bowel down to the anus while preserving normal sphincter function. Objectives: Present study aimed to determine a better procedure of pull through operative procedure for Hirschsprung’s disease by a randomized comparison. Patients and Methods. This interventional study was performed in the department of Paediatric Surgery, Rajshahi Medical College Hospital, Rajshahi, Bangladesh, over a period of one year (from March 2022 to April 2023). A total of 53 patients who were suffering from short segment Hirschsprung’s disease, were included in present study as per inclusion and exclusion criteria and randomized into two groups under study, namely; Laparoscopic assisted transanal pull-through and Duhamel pull-through operations. Primary outcome measured by persistent obstructive symptoms, anastomotic strictures, persistent or acquired aganglionosis and fecal incontinence. Results: Early per operative and postoperative complications, including bleeding, infection, injury to adjacent organs were not troublesome but differences in two groups under study, were significant and findings were in favour of laparoscopic procedure. Persistent obstructive symptoms and aganglionosis occurred in greater percentage in Duhamel procedure but anastomotic strictures and fecal incontinence were commoner in percentage in the laparoscopic variant. Conclusion: The advantages of laparoscopic assisted transanal pull-through include its improved cosmesis, reduced hospital costs, hospital stay, operating time. But anastomotic strictures and fecal incontinence remain as a critical issue for long term outcome. Journal of Paediatric Surgeons of Bangladesh (2018) Vol. 9 (1&2): 21-27